Comparisons of different cooling systems for thermal management of lithium-ion battery packs: Phase change material, nano-enhanced channel cooling and hybrid method - Dilbaz, Furkan; Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2024)
Heat produced during the charging/discharging cycle must be dissipated for lithium-ion batteries to operate efficiently. Consequently, three distinct li-ion battery cooling systems were devised in this research, including phase-changing material (PCM), liquid-assisted, and hybrid, to allow lithium-ion batteries to run at the optimal operating temperature. To assess the efficiency of BTMS, the highest temperature and variation in temperature were examined. Without cooling system, simulations of the 20 Ah capacity battery pack were performed at various discharge rates (2C, 3C, and 4C). After that, an effective thermal management technique was identified by simulating PCM, liquid-assisted, and hybrid BTMS. The efficacy of PCM and BTMS was investigated at three different discharge rates. Water and Al2O3 nanofluid cooling medium thermal performance was investigated for liquid-supported BTMS at four distinct Reynolds numbers (Re) (250, 500, 750, and 1000), three distinct volume ratios (0.5 %, 1 %, and 2 %), and four distinct nanoparticle geometric shapes (Oblate spheroid, block, cylinder, and platelet). The influence of cooling channels on the thermal characteristics on PCM was investigated utilizing four various Re values and three distinct volume ratios, as well as the cooling effectiveness of hybrid BTMS. When the findings were analyzed, it emerged that hybrid BTMS improved the highest temperature by 28 %, while PCM and liquid-assisted cooling techniques enhanced peak temperature by 26 % and 27 %, correspondingly. However, when the temperature difference was analyzed, it was determined that only the hybrid and PCM reduced it to less than 5 degrees C, which is a suitable temperature difference. Paraffin can be cooled more efficiently by lowering the liquid stage distribution in the solid stage and the melting start time utilizing the hybrid cooling technique. Because of this, it has been determined that hybrid BTMS is the optimal cooling approach for the battery module.
Keywords: Battery thermal management; PCM; Nanofluid; Nanoparticle shape; Hybrid cooling